The Ratification of the International Covenant on Economic, Social and Cultural Rights in South Africa - Brand, Danie (Jacobus Frederick Daniel, 1968- ) (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2014.